2022
DOI: 10.1088/1748-9326/ac6313
|View full text |Cite
|
Sign up to set email alerts
|

Environmental justice criteria for new land protection can inform efforts to address disparities in access to nearby open space

Abstract: Substantial funding is being allocated to new land protection and access to protected open space for marginalized communities is a crucial concern. Using New England as a study area, we show striking disparities in the distribution of protected open space across multiple dimensions of social marginalization. Using a quartile-based approach within states, we find that communities in the lowest income quartile have just 52% as much nearby protected land as those in the most affluent quartile. Similarly, communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Among them are often measures of the environment (e.g., ecosystem service provision) and demography (e.g., poverty levels, access to open space). 32 Understanding environmental justice inequities will allow us to address the issue of disadvantaged communities and assist regional planning organizations, environmental justice networks and scholars, and state and federal agencies in enacting change and adopting more fair and equitable practices as we progress. 33 If harmful activities have an outsized impact on a hotspot of injustice or its resources are exhausted, it lacks social-ecological recognition and participation.…”
Section: The Understanding and Challenges Social Justice In The Conte...mentioning
confidence: 99%
“…Among them are often measures of the environment (e.g., ecosystem service provision) and demography (e.g., poverty levels, access to open space). 32 Understanding environmental justice inequities will allow us to address the issue of disadvantaged communities and assist regional planning organizations, environmental justice networks and scholars, and state and federal agencies in enacting change and adopting more fair and equitable practices as we progress. 33 If harmful activities have an outsized impact on a hotspot of injustice or its resources are exhausted, it lacks social-ecological recognition and participation.…”
Section: The Understanding and Challenges Social Justice In The Conte...mentioning
confidence: 99%
“…This entails ensuring that all individuals bear a fair and equitable burden of environmental pollution and associated health risks while enjoying equal opportunities to use ecological amenities. 37 There exist numerous issues that are interconnected with urban environmental justice. These factors include frequent indicators of the environment, such as the supply of ecosystem services, and demographic aspects, such as poverty rates and access to open spaces.…”
Section: Environmental Justice In Environment Regulation With Restora...mentioning
confidence: 99%
“…Jennings et al 2012; Trust for Public Land 2020; Chapman et al 2021). In the New England region, Sims et al (2022) found substantial disparities in access to nearby protected open space at the census tract level: communities with the lowest income or the highest proportions of people of color defined by quartiles had just half as much nearby protected land as those in the opposite quartiles. An analysis of 37 cities across the US by Locke et al (2021) showed that current patterns of urban tree canopy were linked to residential segregation patterns determined by historical redlining, with substantially less investment in trees for communities of color.…”
Section: Introductionmentioning
confidence: 99%
“…Future research can play an important role in providing information that can help to assess current disparities in the distribution of benefits or that can be used to develop screening tools to identify conservation opportunities (e.g. Sims et al 2022). Research can also illuminate how the explicit inclusion of social justice as a goal of land protection is likely to shift conservation priorities, processes, and outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation